A multicentre analytical comparison study of inter‐reader and inter‐assay agreement of four programmed death‐ligand 1 immunohistochemistry assays for scoring in triple‐negative breast cancer. Issue 4 (27th November 2020) - Noske, Aurelia; Ammann, Johannes U; Wagner, Daniel‐Christoph; Denkert, Carsten; Lebeau, Annette; Sinn, Peter; Kreipe, Hans‐Heinrich; Sommer, Ulrich; Baretton, Gustavo; Steiger, Katja; Kiechle, Marion; Hieke‐Schulz, Stefanie; et al.
Abstract : Aims: Studies in various cancer types have demonstrated discordance between results from different programmed death‐ligand 1 (PD‐L1) assays. Here, we compare the reproducibility and analytical concordance of four clinically developed assays for assessing PD‐L1‐positivity in tumour‐infiltrating immune cells in the tumour area (PD‐L1‐IC‐positivity) in triple‐negative breast cancer (TNBC). Methods and results: Primary TNBC resection specimens ( n =  30) were selected based on their PD‐L1‐IC‐positivity per VENTANA SP142 (<1%: 15 cases; 1–5%: seven cases; >5%: eight cases). Serial histological sections were stained for PD‐L1 using VENTANA SP142, VENTANA SP263, DAKO 22C3 and DAKO 28‐8. PD‐L1‐IC‐positivity and tumour cell expression (≥1 versus <1%) were scored by trained readers from seven sites using online virtual microscopy. The adjusted mean of PD‐L1‐IC‐positivity for SP263 (7.8%) was significantly higher than those for the other three assays (3.7–4.9%). Differences in adjusted means were statistically significant between SP263 and the other three assays ( P  < 0.0001) but not between the three remaining assays when excluding SP263 ( P =  0.0961–0.6522). Intra‐class correlation coefficients revealed moderate‐to‐strong inter‐reader agreement for each assay (0.460–0.805) and poor‐to‐strong inter‐assay agreement for each reader (0.298–0.678) on PD‐L1‐IC‐positivity. Conclusions: In this first multicentre study of different PD‐L1 assays in TNBC, we show that PD‐L1‐IC‐positivity for SP142, 22C3 and 28‐8 was reproducible and analytically concordant, indicating that these three assays may be analytically interchangeable. The relevance of the higher PD‐L1‐IC‐positivity for SP263 should be further investigated.